Controlling the Properties of Metal Films Deposited Using Magnetron Sputtering Systems with Evaporative Targets; Surface Modification of Materials by Ion Beams (SMMIB-2019) - Bleykher (Bleicher) G. A. Galina Alekseevna; Yuryeva A. V. Alena Victorovna; Sidelev D. V. Dmitry Vladimirovich; Shabunin A. S. Artem Sergeevich; Yuriev Yu. N. Yuri Nikolaevich (Ion-Assisted Coating Deposition. Poster Session, 2019)
Заглавие с экрана